Identifikasi Kandungan Sulfur, Saponin, dan Kardiak Glikosida pada Tapai Singkong - Fiona, Fiona; Arza, Seti; Ega, Ega; Novita, Novita; Darmawan, Bambang (Program Studi Teknologi Hasil Pertanian Fakultas Sains dan Teknologi Hasil Pertanian Universitas Muhammadiyah Sidenreng Rappang, 2024)
This study aims to analyze the sulfur, saponin, and cardiac glycoside content in cassava tapai using three different processing methods: steamed tapai, plastic-wrapped tapai, and boiled tapai. Chemical tests were conducted to identify the presence of these three components in two separate trials for each sample. The test results revealed that none of the three types of tapai contained sulfur. However, plastic-wrapped tapai showed a significant presence of saponin, with the test results indicating a considerable amount (++), in the first trial and a moderate amount (+) in the second trial. Meanwhile, no saponin was found in either steamed or boiled tapai. Additionally, cardiac glycosides were detected in all three types of tapai, in both the first test and the repeated test, with results consistently showing (+) for all samples. This study provides insight into the differences in chemical composition based on the processing method used, which can influence the nutritional value and functional properties of cassava tapai.